Robber flies (Diptera: Asilidae) of South Korea. Parts VI–VIII. South Korean species of the Subfamilies Dasypogoninae, Dioctriinae and Trigonomiminae - Young, Charles L.; Hradský, Milan M. (Zootaxa, 2008)
Seven species belonging to the subfamilies Dasypogoninae Macquart, Dioctriinae Enderlein, and Trigonomiminae Enderlein, are recorded from South Korea. New records include the subfamilies Dioctriinae and Trigonomiminae; the genera Dioctria Meigen, and Damalis Fabricius, and the species: Dioctria aestivis Esipenko, Dioctria humeralis eoa Lehr, Dioctria keremza Richter, Dioctria vainsteini Lehr, and Damalis andron Walker. Drawings of diagnostic features, a current check list of South Korean asilids, keys and descriptions are included.